Reshaping surgical specialist training in small animal surgery during and after the COVID‐19 pandemic. Issue 5 (25th May 2021) - Alexander, Akash; Radke, Heidi
Abstract: Objective: To assess the perceived effects of the COVID‐19 pandemic on small animal surgical specialist training, among trainees and supervisors and to propose changes, based upon the results, that could be incorporated into training programs. Study Design: Anonymous online questionnaire survey. Sample Population: Eighty‐one eligible responses were collected in September 2020, including 52 European College of Veterinary Surgeons (ECVS) residents and 29 ECVS Diplomates acting as supervisors. Methods: Descriptive statistics were used to analyze the data. Fisher's exact test was used to test for significance. Results: A reduction in surgical case load was reported by 82% ( n  = 66/81) of respondents, with 82% ( n  = 54/66) of those believing that COVID‐19 had a mild‐to‐moderate impact on training. Compared to supervisors, residents were less likely to feel that appropriate guidance, a safe working environment, and measures to preserve training had been provided ( p  < .01). Only 45% ( n  = 22/49) of residents reported confidence with performing teleconsultations. Ninety percent ( n  = 73/81) of respondents considered online "case presentations" and "edited surgical video footage" as a positive ancillary tool. Conclusion: COVID‐19 has resulted in a reduction in case load and training for the majority of residents. A discrepancy between the opinions of residents and supervisors was noted on various aspects of COVID‐19 related effects. Impact: Open communication, as well as the use of additional training tools through digital platforms may help to preserve safe and effective training during times of decreased clinical activity. While this study has focused on surgical specialist training, the results could be applied to other disciplines.